Age-Related Differences in the Effect of Prolonged Vibration on Maximal and Rapid Force Production and Balance Ability - Ema, Ryoichi; Kanda, Akihiro; Shoji, Mikio; Iida, Natsuki; Akagi, Ryota (Frontiers in Physiology, 2020)
We tested the hypothesis that older adults would not likely experience deficits in maximal and explosive plantar flexion strength and standing balance performance induced by prolonged Achilles tendon vibration compared with young adults. Fifteen older men (OM, 73 ± 5 years) and 15 young men (YM, 24 ± 4 years) participated in two interventions on different days: lying in a quiet supine position for 30 min with or without prolonged vibration to the Achilles tendon. Before and after the interventions, maximal voluntary contraction (MVC) torque during plantar flexion, rate of torque development (RTD), and center of pressure (COP) speed during single-leg standing were measured. The root mean square of the electromyogram (RMS-EMG) during performance and V-wave and voluntary activation during MVC were assessed. The MVC torque (7 ± 7%) and RTD (16 ± 15%) of YM but not OM significantly decreased after vibration. In addition, the relative changes observed in YM positively correlated with changes in RMS-EMG of the medial gastrocnemius (MG) (MVC torque and RTD) and in MG V-wave and voluntary activation (MVC torque). COP speed significantly increased (16 ± 20%) in YM only after vibration and was accompanied by increased activation of the lateral gastrocnemius. This is the first study to show that the effects of prolonged Achilles tendon vibration on strength and balance performances were apparent in young adults only. The differences between the age groups may be related to the attenuated gastrocnemius neuromuscular function in older adults.